2021
DOI: 10.3389/fimmu.2021.719807
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Microglial α-Synuclein/TLRs/NF-kappaB/NLRP3 Inflammasome Axis in Parkinson’s Disease

Abstract: According to emerging studies, the excessive activation of microglia and the subsequent release of pro-inflammatory cytokines play important roles in the pathogenesis and progression of Parkinson’s disease (PD). However, the exact mechanisms governing chronic neuroinflammation remain elusive. Findings demonstrate an elevated level of NLRP3 inflammasome in activated microglia in the substantia nigra of PD patients. Activated NLRP3 inflammasome aggravates the pathology and accelerates the progression of neurodeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 179 publications
2
54
0
Order By: Relevance
“…The NLRP3 inflammasome, an important component of inflammation, is a complex of multiple proteins, including NLRP3, ASC and caspase-1, which are expressed abundantly in microglia [ 17 , 45 ]. When stimulated, the NLRP3 complex leads to caspase-1 activation, promotes the maturation and secretion of the proinflammatory cytokines IL-1β and IL-18, and induces the shift of microglia into an anti-inflammatory state [ 46 ], while inhibition the NLRP3 inflammasome suppresses microglial polarization to a proinflammatory state [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NLRP3 inflammasome, an important component of inflammation, is a complex of multiple proteins, including NLRP3, ASC and caspase-1, which are expressed abundantly in microglia [ 17 , 45 ]. When stimulated, the NLRP3 complex leads to caspase-1 activation, promotes the maturation and secretion of the proinflammatory cytokines IL-1β and IL-18, and induces the shift of microglia into an anti-inflammatory state [ 46 ], while inhibition the NLRP3 inflammasome suppresses microglial polarization to a proinflammatory state [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exome sequencing analysis of human NLRP3 gene variants revealed that multiple single-nucleotide polymorphisms were associated with a significantly reduced risk of PD development [ 15 ]. Moreover, inhibiting the NLRP3 inflammasome can reduce α-synuclein deposition, alleviate dopaminergic neuron damage and improve motor function [ 11 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…4 ). We demonstrated that the cytosolic release of mtDNA induced by K + efflux in macrophages activates NLRP3 inflammasome and raises the possibility that dysregulated mitochondria as a therapeutic target for NLRP3 inflammasome-regulated diseases [ 7 , [38] , [39] , [40] ].
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that the expression level of MBLs protein in the cerebrospinal fluid of AD patients is significantly reduced ( Moller-Kristensen et al, 2006 ), and the expression level of the anti-inflammatory factor Fetuin-A in the plasma of patients with mild to moderate AD is also significantly reduced ( Smith et al, 2011 ). Inflammatory targets for Parkinson’s Disease (PD) disease currently include α-synuclein and vitamin D ( Gambino et al, 2019 ; Li et al, 2021 ), both of which are also significantly down-regulated in the peripheral blood of PD patients. In addition, some studies have found that the blood brain barrier (BBB) of patients with neurodegenerative diseases is damaged, and the exosomes secreted by abnormally activated microglia can enter the peripheral blood through the BBB, and the contents contained in the exosomes can be detected ( Guo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%